BASIC PRINCIPLES OF PRODUCTION-AND-TECHNICAL POTENTIAL CAPACITY FORMATION IN THE CONSTRUCTION INDUSTRY OF A REGION - Bredikhina, Natalia Vladimirovna (Journal of Applied Engineering Science, 2017)
The paper discusses a structural model of potential capabilities and development patterns of a regional production-and-technical potential capacity of construction industry organizations. The model utilizes quantitative assessment of a maximal possible efficiency of resource utilization by a construction organization.